Phase 1 Study of the Safety, Tolerability, and Pharmacokinetics of the β-Lactamase Inhibitor Vaborbactam (RPX7009) in Healthy Adult Subjects - Griffith, David C.; Loutit, Jeffery S.; Morgan, Elizabeth E.; Durso, Stephanie; Dudley, Michael N. (Antimicrobial agents and chemotherapy, 2016)
Vaborbactam (formerly RPX7009) is a member of a new class of β-lactamase inhibitor with pharmacokinetic properties similar to those of many β-lactams, including carbapenems. The pharmacokinetics and safety of vaborbactam were evaluated in 80 healthy adult subjects in a first-in-human randomized, placebo-controlled, double-blind, sequential single- and multiple-ascending-dose study. A total of 10 dose cohorts were enrolled in the study, with 6 subjects randomized to receive 250 to 2,000 mg of vaborbactam and 2 subjects randomized to receive placebo in each cohort. Maximum concentrations for vaborbactam were achieved at the end of the 3-h infusion. Vaborbactam exposure ( C max and area under the concentration-time curve [AUC]) increased in a dose-proportional manner following multiple doses. There was no evidence of accumulation with multiple doses, consistent with the terminal half-life of ∼2 h. Both the volume of distribution ( V ss ) and plasma clearance were independent of dose. For the 2,000-mg dose, the plasma clearance was 0.17 ± 0.03 liters/h, the AUC from 0 h to infinity (AUC 0–∞ ) was 144.00 ± 13.90 mg · h/liter, and the V ss was 21.80 ± 2.26 mg · h/liter. Urinary recovery was 80% or greater over 48 h across all dose groups. No subjects discontinued the study due to adverse events (AEs), and no serious AEs (SAEs) were observed. All AEs were mild to moderate and similar among the vaborbactam- and placebo-treated subjects, with mild lethargy as the only unique AE reported with the high dose of vaborbactam. Overall, this study revealed the safety, tolerability, and pharmacokinetic profile of vaborbactam and formed the basis for advancement into patient studies in combination with meropenem, including treatment of patients with carbapenem-resistant Enterobacteriaceae (CRE) infections. (This study is registered at ClinicalTrials.gov under identifier NCT01751269.)